The Effectiveness of Legal Aid Standards for Suspects in the Indonesian Criminal Justice System in Achieving Access to Justice - Tri Utami, Nurani Ajeng; Oktobrian, Dwiki; Dwi Cahyani, Enny; Turnip, Gebi Emada; Safitri, Fadia Rahma (Fiat Justisia: Jurnal Ilmu Hukum, 2024)
The implementation of legal aid service standards, as outlined in Regulation No. 4 of 2021 by the Minister of Law and Human Rights of Indonesia, was expected to enhance the quality of legal aid services. However, in reality, suspects continue to experience inconsistent access to their rights, especially within the criminal justice system. This study aims to investigate the application of these standards across the police, prosecutor's office, and court sectors. Employing an empirical juridical approach with a qualitative and comparative study method, data was gathered through interviews and literature review, then analyzed using content and comparative analysis techniques. The findings reveal that the enforcement of legal aid service standards in the criminal justice system has been ineffective, marked by frequent violations of suspects' rights. These violations include providing indirect assistance, inadequate representation at various stages of trials, appointing advocates not affiliated with accredited LBH (Legal Aid Institute), and advocates displaying insufficient responsiveness and engagement in assisting suspects. Such violations significantly hinder suspects' access to justice within the criminal justice system.